Cognitive effects of non-surgical brain stimulation for major depressive disorder: protocol for a systematic review and meta-analysis. Issue 2 (5th February 2019) - Kiebs, Maximilian; Hurlemann, René; Mutz, Julian
Abstract : Introduction: Non-surgical brain stimulation techniques may be considered as alternative or add-on treatments for patients with major depressive disorder who failed to respond to pharmacological interventions. Electroconvulsive therapy has been shown to be highly effective in reducing depressive symptoms but stakeholders remain concerned about adverse cognitive effects. Repetitive transcranial magnetic stimulation and transcranial direct current stimulation may be associated with more benign adverse effect profiles and may indeed improve certain cognitive functions such as memory and attention. To guide clinical decision-making, we will carry out a systematic review and meta-analysis of the cognitive effects of eight non-surgical brain stimulation techniques. Methods and analysis: A systematic literature search of the Embase, PubMed/MEDLINE and PsycINFO databases, the Cochrane Central Register of Controlled Trials, ClinicalTrials.gov and OpenGrey will be performed. We will include both randomised clinical trials which report on at least one cognitive measure post treatment as well as non-randomised trials and pre-post intervention studies. There are no restrictions to the type of cognitive outcome measures, except that the tests are standardised and psychometrically validated. The Revised Cochrane tool for assessing risk of bias in randomised trials (RoB 2.0) will be used to evaluate included trials. Pre-post studies will be evaluated using the quality assessment tool developed by the US National Heart, Lung and Blood Institute. Meta-analysis, meta-regression, subgroup and sensitivity analyses will be conducted where sufficient data are available. Ethics and dissemination: No ethical approval is needed to conduct this work. The findings will be submitted for publication in peer-reviewed journals and presented at scientific meetings. PROSPERO registration number: CRD42018118850.